HLA-A2 Phenotype may be Protective Against Graves’ Disease but not Against Hashimoto’s Thyroiditis in Caucasians - Bernecker, C.; Ostapczuk, M.; Vordenbäumen, S.; Ehlers, M.; Thiel, A.; Schinner, S.; Willenberg, H.; Scherbaum, W. A.; Schott, M. (Hormone and Metabolic Research, 2013)
Graves’ disease (GD) and Hashimoto’s thyroiditis (HT) are the most common autoimmune thyroid diseases (AITDs) affecting up to 5% of the general population. In Caucasians HT has a prevalence of up to 4.60% and GD a prevalence of 1–2%. The aim of this study was to investigate the association between HLA-A2 and the AITDs GD and HT among Caucasians. HLA alleles of 33 patients with GD and 75 patients with HT were determined by serological typing. The frequency of HLA A2 was significantly reduced in GD (p=0.033) but not in HT (p=n.s.) as compared to control samples. In individuals positive for HLA-A2 odds ratio for protection from GD was found to be 2.8. This study supports the hypothesis that genetic predisposition to GD is not restricted to MHC class II molecules. The significant negative association between HLA A2 and GD supports the hypothesis that MHC class I genes may be relevant for the protection from GD. In contrast the nonsignificant results for HT indicate that this association may not apply to AITDs in general.
Keywords: autoimmune thyroiditis; Graves’ disease; Hashimoto’s thyroiditis; major histocompatibility complex (MHC); autoimmunity; thyroid epidemiology